If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 11) = 5(21 + -1x) Reorder the terms: 5(11 + x) = 5(21 + -1x) (11 * 5 + x * 5) = 5(21 + -1x) (55 + 5x) = 5(21 + -1x) 55 + 5x = (21 * 5 + -1x * 5) 55 + 5x = (105 + -5x) Solving 55 + 5x = 105 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 55 + 5x + 5x = 105 + -5x + 5x Combine like terms: 5x + 5x = 10x 55 + 10x = 105 + -5x + 5x Combine like terms: -5x + 5x = 0 55 + 10x = 105 + 0 55 + 10x = 105 Add '-55' to each side of the equation. 55 + -55 + 10x = 105 + -55 Combine like terms: 55 + -55 = 0 0 + 10x = 105 + -55 10x = 105 + -55 Combine like terms: 105 + -55 = 50 10x = 50 Divide each side by '10'. x = 5 Simplifying x = 5
| 54=3(2-2x) | | X*X*Y*Y=1600 | | x+4=0.6(2x-7) | | tn=tn-1+6 | | h(6)ifh(x)=x^2-2x-5 | | 8x+9-7x=11 | | 7(3x-9)=-63 | | B=4m+6 | | 21-6x=9-9x | | tn=tn-1+2 | | x+4=0.5(2x-7) | | 5q+p=q-3 | | 3(7x+9)=48 | | x^2+y^2=1600 | | 7*[3(3)-2]+5=6*[2(3)-1]+24 | | 2cos^2-5cos-3=0 | | 6=-3+33 | | k-15=-30 | | tn=3n-1 | | 9+4x=23 | | 4X+11=2X^2+13X+6 | | -7(-6x+2)=48 | | 5(x+11)=5(12-x) | | 4x+9=-31-4x | | e-6=7 | | tn=tn-1-4 | | 4(-7+2x)=-28 | | 3(3-y)1=31 | | -4x^3+4x^2+35x=0 | | 2-a=3 | | 4x-23x+18x-278=34 | | x^2-1040x=0 |